2018
DOI: 10.1021/acs.jmedchem.8b01327
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Biological, and Structural Explorations of New Zwitterionic Derivatives of 14-O-Methyloxymorphone, as Potent μ/δ Opioid Agonists and Peripherally Selective Antinociceptives

Abstract: Herein, the synthesis and pharmacological characterization of an extended library of differently substituted N-methyl-14-O-methylmorphinans with natural and unnatural amino acids and three dipeptides at position 6 that emerged as potent μ/δ opioid receptor (MOR/DOR) agonists with peripheral antinociceptive efficacy is reported. The current study adds significant value to our initial structure–activity relationships on a series of zwitterionic analogues of 1 (14-O-methyloxymorphone) by targeting additional amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 66 publications
0
29
0
Order By: Relevance
“…The in vitro functional opioid profile of the new OP-NT hybrid peptides ( 3 – 12 ) to the human opioid receptors was next determined in the guanosine-5′- O -(3-[ 35 S]thio)-triphosphate ([ 35 S]GTPγS) binding assays using membranes from CHO cells stably expressing the human MOR, DOR, or KOR, performed as described. 28 Generally, lower MOR potencies were observed for the new OP-NT hybrids when compared to the parent opioid tetrapeptide KGOP01 , with the largest decreases observed in DOR and KOR agonist potencies ( Table 3 ). Furthermore, the in vitro functional results correlate well with the observations from radioligand binding studies, with the addition of an NT sequence to the opioid tetrapeptide KGOP01 affecting both binding and activation of the opioid receptors.…”
Section: Results and Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The in vitro functional opioid profile of the new OP-NT hybrid peptides ( 3 – 12 ) to the human opioid receptors was next determined in the guanosine-5′- O -(3-[ 35 S]thio)-triphosphate ([ 35 S]GTPγS) binding assays using membranes from CHO cells stably expressing the human MOR, DOR, or KOR, performed as described. 28 Generally, lower MOR potencies were observed for the new OP-NT hybrids when compared to the parent opioid tetrapeptide KGOP01 , with the largest decreases observed in DOR and KOR agonist potencies ( Table 3 ). Furthermore, the in vitro functional results correlate well with the observations from radioligand binding studies, with the addition of an NT sequence to the opioid tetrapeptide KGOP01 affecting both binding and activation of the opioid receptors.…”
Section: Results and Discussionmentioning
confidence: 93%
“…Binding of [ 35 S]GTPγS to membranes from CHO stably expressing the human opioid receptors was conducted according to the published procedures. 28 Cell membranes were prepared in buffer A (20 mM HEPES, 10 mM MgCl 2 , and 100 mM NaCl, pH 7.4) as described for competitive radioligand binding assays. Cell membranes (5–10 μg) in buffer A were incubated with 0.05 nM [ 35 S]GTPγS, 10 μM GDP, and various concentrations of test peptides in a final volume of 1 mL for 60 min at 25 °C.…”
Section: Methodsmentioning
confidence: 99%
“…There is substantial evidence demonstrating the involvement of peripheral ORs in MOR agonists-induced analgesia following systemic administration in acute thermal pain models in rat or mouse [34,42]. Research from our laboratory (Schmidhammer and Spetea's, Al-Khrasani and Fürst's and Benyhe's research teams) and others have reported on effective, peripheral analgesic effects of opioids following local or systemic administration applying various pharmacological approaches in rodent models of inflammatory and visceral pain [2,[35][36][37][38][39][43][44][45][46][47][48][49][50][51][52][53]. On the other hand, in animal models of neuropathic pain, the peripheral analgesic effect of opioids is a question of debate [54][55][56][57][58][59].…”
Section: Contribution Of Peripheral Mors To Opioid-induced Analgesia and Analgesic Tolerancementioning
confidence: 99%
“…In opioid research as well as other drug discovery areas, the limited access of substances to the CNS can be achieved by either quaternization of the molecule or the introduction of functional groups endowing the molecule to have a zwitterionic structure at body pH (Table 1) [34][35][36][37]47,[60][61][62][63][64][65]. The number of MOR agonists with limited CNS penetration and displaying peripheral analgesia have been increasing over the years, but they have not been proven so far to be of clinical value [43,52,66,67].…”
Section: Contribution Of Peripheral Mors To Opioid-induced Analgesia and Analgesic Tolerancementioning
confidence: 99%
See 1 more Smart Citation